Nexie - Cawthon, Scott, 1971-; Parra, Kelly; Waggener, Andrea Rains, 1960- (Cawthon, Scott, 1971- Five nights at Freddy's. Tales from the pizzaplex, 2023)
"Can you keep a secret?... Astrid doesn't tell anyone about the strange things her Buddytronic doll has been up to. Kara convinces a Pizzaplex employee no one will know if he lets her spend a little more time in the VR attraction. And a Fazbear Entertainment engineer's custom project has surprises in store for anyone who encounters it. But in the world of "Five Nights at Freddy's," secrets never stay hidden for long. This sixth volume spins three sinister novella-length tales from uncharted corners of the series." -- Page [4] of cover.